Advances in water quality monitoring and assessment in marine and coastal regions - Bergamasco, Alessandro (2021)
Coastal environments include several different habitat typologies, from shorelines to estuaries, and rocky and muddy environments. All these ecosystems are very vulnerable to anthropogenic pressures, climate fluctuations, stressing the need to monitor their quality status and suggest possible measures for the remediation and recovery of their natural equilibria. In the light of these considerations, this Special Issue (SI) collects a number of multi-faceted scientific contributions on the quality of aquatic ecosystems, with a particular focus on the transitional environments where marine and terrestrial habitats are in close relationship.